(untitled) (Journal of Life and Earth Science, 2012)
With a view to gather information on the diversity, habitat, distribution and residential status of avifauna of Joypurhat District under Rajshahi Division, a systematic field study was conducted for a period of eight months from April to November 2010. The study area was divided into the following five Upazila sites viz. Site A Joypurhat Sadar; Site B Khetlal; Site C Panchbibi; Site D Akkelpur and Site E Kalai. A total of 57 species, belonging to 8 orders, 28 families and 48 genera, were recorded. Of 57 species, 47.37% were non-passerines and 52.63% passerines; 89.43% were resident and 11.57% migratory. The status of the birds ranged from 14.04% for fairly common to 45.61% for rare species. The diversity of the bird species ranged from 25 (47.37%) for site D to 39 (68.42%) for site A. The study revealed that most of the species used more than one habitat and the highest number of species, 52 (91.23%), was observed on the trees, whereas the lowest number of species, 3 (5.26%), was found around the ponds. A number of environmental and man-made factors appeared to be responsible for declining population and species diversity of the birds in the study area. DOI: http://dx.doi.org/10.3329/jles.v6i0.9721 JLES 2011 6: 51-57